In vitro propagation of an epiphytic and rare orchid Eria bambusifolia Lindl. - Basker, S.; Narmatha Bai, V. (Research in Biotechnology, 2010)
Orchids seeds are minute, unique lacking storage tissues and they are marveled for their mystic shapes and colour for centuries. Asymbiotic seed germination opened up new avenues in rescuing of orchids from their wild population. In the present study, an epiphytic and rare orchid Eria bambusifolia seeds were germinated in two different Knudson (KC) and Murashige and Skoog’s (MS) medium. Higher germination percentage was noted in MS medium so it was selected for further studies. The MS medium was nourished with different phytohormones and NAA at 2 mg/l was found to enhance shoot and root length. The rooted seedlings were acclimatized successfully.